Structure-Dependent Performance of N-Doped TiO2 Nanowires toward Efficient Solar-Driven Hydrogen Production - Evan Attalario; Resha Mutia Rahma; Yuly Kusumawati; Atthar Luqman Ivansyah; Yulia Eka Putri; Diana Vanda Wellia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This research focuses on enhancing hydrogen production via the photocatalytic method using a TiO2 catalyst with nitrogen doping and morphology modification to improve efficiency. Nitrogen-doped TiO2 nanowires (NTN) were successfully hydrothermally grown on titanium foil to produce thin-film photocatalysts for the visible-light-driven production of hydrogen. Nitrogen incorporation induced bandgap narrowing, from 3.18 eV to 2.85 eV, by introducing N 2p states close to the valence band, thereby increasing visible-light absorption. Structural analyses confirmed the formation of lattice strain and oxygen vacancies associated with substitutional doping, while the one-dimensional nanowire architecture enhanced charge transport and reduced carrier recombination pathways. The optimized N–TiO2 NWs demonstrated the highest hydrogen evolution rate of 2.385 µmol/cm2 under 180 minutes of visible-light irradiation, corresponding to a hydrogen evolution rate of 0.795 µmol/cm²/h, without a noble-metal co-catalyst. A strong correlation is established between nitrogen-induced surface electronic modification and the enhancement of nanowire-driven charge separation. This study presents a recyclable and scalable thin-film photocatalyst design suitable for future solar hydrogen production systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).